Prophylactic low-molecular-weight heparin administration protected against severe acute pancreatitis partially by VEGF/Flt-1 signaling in a rat model. (October 2020) - Li, S; Zhang, S; Li, R; Chen, S; Chang, S; Chen, X; Li, Y; Su, X; Wu, T; Xu, M
Background: The present study was aimed to explore the effects and the underlying mechanism of prophylactic low-molecular-weight heparin (LMWH) treatment on taurocholate-induced severe acute pancreatitis (SAP) in a rat model. Methods: Rat SAP model was induced by injection of 4% sodium taurocholate into the pancreatic duct. LMWH was applied half an hour before the induction of pancreatitis at the dose of 200 IU/kg subcutaneous injection. The rats were euthanized at 1 h, 6 h, and 12 h after taurocholate-induced SAP. The inflammatory and oxidative response markers were assessed. And the vascular endothelial growth factor (VEGF) and Fms-related tyrosine kinase 1 (Flt-1) expression were evaluated by immunohistochemistry (IHC) and western blot methods. Results: The expression of inflammatory and oxidative response markers increased after induction of SAP. IHC and western blot results showed the VEGF and Flt-1 expression were increased in SAP group. Prophylactic LMWH administration reduced the inflammatory and oxidative response markers expression and decreased the expression of VEGF and Flt-1. Conclusions: This study suggested that prophylactic LMWH treatment mitigated the severity of pancreatitis in rat SAP model by anti-inflammation and oxidative response. The underlying mechanism may result from downregulating VEGF/Flt-1 signaling of LMWH in SAP rat model.